Programmable control for setting voltage and current in neuronal membranes. - Blancas Núñez, Jorge; Valdiosera, Rene F. (Revista Mexicana de Ingenieria Biomedica, 1991)
The equipment that is described has the purpose of contributing to the study of the electrical activities of the intermittent bursts type neurons. At present, no equipment similar to the one presented is commercially available. The solution found is based on the use of a microcontroller which facilitates and reduces the proposed circle.